2013
DOI: 10.1021/jp310332y
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Oxygen Chemisorption on Carbon Nanotubes Revisited with Theory and Experiment

Abstract: Density-functional-theory based calculations of two single-walled carbon nanotubes of different chirality settle open issues on the sidewall chemisorption of atomic oxygen at low concentrations. Ether groups are the thermodynamically favored configurations. If kinetically trapped in epoxide groups, oxygen introduces characteristic new levels in the gap of the nanotube that are detected with scanning tunneling spectroscopy experiments. Discrepancies with previous predictions are shown to originate from the inad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…On (12,0) carbon nanotubes, ether-like structures are predicted for the oxygen adsorption on both a defect-free surface and a defective surface in the presence of an SW defect (Figure 1g,h). Consistent with the previous work on (10,0) defect-free nanotubes, 60 O adsorption on the bridge site of an axis C−C bond with the formation of an epoxide is more endothermic by 0.15 eV as compared to that on a zigzag C−C bond, where ether formation is favored. The presence of an SW defect lowers the adsorption energy by 0.7 eV (Figure 1h).…”
Section: ■ Computational Methodssupporting
confidence: 89%
“…On (12,0) carbon nanotubes, ether-like structures are predicted for the oxygen adsorption on both a defect-free surface and a defective surface in the presence of an SW defect (Figure 1g,h). Consistent with the previous work on (10,0) defect-free nanotubes, 60 O adsorption on the bridge site of an axis C−C bond with the formation of an epoxide is more endothermic by 0.15 eV as compared to that on a zigzag C−C bond, where ether formation is favored. The presence of an SW defect lowers the adsorption energy by 0.7 eV (Figure 1h).…”
Section: ■ Computational Methodssupporting
confidence: 89%
“…The solution should come from ab initio calculations. Only recently, however, we have shown that at very low coverage atomic oxygen highly prefers ether configurations on the sidewall of a SWNT of ∼1 nm diameter and that using atomistic models of small sizes severely affects the ET-EP energy differences . Moreover, with a joint computational (DFT-based) and experimental (scanning-tunneling spectroscopy (STS)) approach, we showed that metastable epoxides can act as effective kinetic traps for oxygen and give rise to characteristic impurity levels in the gap of the nanotube.…”
Section: Introductionmentioning
confidence: 99%
“…However, the success of the reactive force-field ReaxFF in the simulation of carbon nanotube growth, and also graphene oxide, suggests that a careful analysis of its performance for oxygen adsorbates on CNTs could be useful at this stage. Following our first encouraging findings, here, we apply the ReaxFF potential to the same problems mentioned above, thus obtaining a detailed comparison with the DFT-PBE results.…”
Section: Introductionmentioning
confidence: 99%
“…1,46 More generally, other studies have shown that chirality is expected to have a direct effect on oxygen sidewall chemisorption and can affect chemical reactivity in general. 47,48 Depending on the etching gas and the particular treatment, there are already some reports indicating that m-CNTs may etch more rapidly with gas-phase oxidants than s-CNTs. 2,36À38,40,49 Using laser irradiation in air, Huang et al observed both the preferential destruction of m-CNTs and high chiral angle s-CNTs.…”
mentioning
confidence: 99%
“…These purely geometric arguments predict faster etch rates for small-diameter nanotubes and do not in themselves explain differences in electronic type, e.g ., differing etch rates for metallic CNTs (m-CNTs) and semiconducting CNTs (s-CNTs). Doping, however, is expected to be as significant a factor as chiral angle. , More generally, other studies have shown that chirality is expected to have a direct effect on oxygen sidewall chemisorption and can affect chemical reactivity in general. , …”
mentioning
confidence: 99%